Cytoplasmic p16 Is Expressed in Normal Brown Fat and Hibernomas. (August 2020) - Karpathiou, Georgia; Dumollard, Jean Marc; Evangelou, Zoe; Batistatou, Anna; Peoc'h, Michel; Papoudou-Bai, Alexandra
White adipose tissue browning has emerged as a putative therapy of obesity, and studies in mice have shown that Cdkn2a is implicated in white-to-brown transition. However, the role of Cdkn2a product p16 has been never studied in human brown fat tissue. The aim of the study is to investigate the expression of p16 in normal brown fat and in hibernoma, a lipoma containing brown fat-like adipocytes. Ten normal brown fat tissues and 5 hibernomas were immunohistochemically studied for p16 expression. Nearby white adipose tissue was used for comparison. All brown fat and hibernomas specimens express p16 in a cytoplasmic manner. Neighboring white adipose tissue is negative for p16 expression. Thus, cytoplasmic p16 may be associated with fat tissue browning.